Fall of Ground Management Through Underground Joint Mapping: Shallow Chrome Mining Case Study - Netshilaphala, Vhutali; Zvarivadza, Tawanda (Springer, 2022)
The use of joint properties and joint mapping techniques are key for fall of ground management in underground mining. This paper outlines the use of probabilistic design approach in addressing potential falls of ground, based on identified keyblocks. A shallow chrome mine was used as a case study to identify potential causes of falls of ground with the aim of improving the existing fall of ground management system. The existing fall of ground management system comprises of visual observations, Ground Penetrating Radar (GPR) scanning and Borehole camera inspections. The mine is characterised by geological structures such as faults and joints, hence the system leans towards structural analysis. Joint mapping was carried out in the North and South sections of the mine using window mapping and scanline mappint techniques. The collected joint data from each section was used to evaluate rock fall probability. Rockfall probabilistic analysis carried out in the study indicates that about 80% of all key blocks formed are 1 m3 in size. Results show that larger blocks are more likely to fail through rotation whereas small key blocks are most likely to fall in-between support units. Further stability analysis was conducted through simulation of the effect of change in support spacing on excavation stability. Indeed support spacing plays a critical role in the overall stability of the excavation as opposed to the length and capacity of the support unit. This conclusion was drawn based on the improvement of the factor of safety during the simulation exercise. This research is based on an MSc Engineering study.